Effect of commercial probiotics and antibiotics on the growth of Campylobacter isolated from chicken meat in Ho Chi Minh city markets - Bao Tran, Pham; Anh Thu, Nguyen; Hang, Tong Thi (Vietnam Journal of Biotechnology, 2023)
This study explores the antibiotic susceptibility of Campylobacter, a prominent foodborne pathogen, isolated in Ho Chi Minh city markets and the efficacy of commercial probiotics in inhibiting these bacteria for enhancing food safety and treating Campylobacter infections. Bacteria were isolated from chicken meat in modified coal deoxycholate cefoperazone agar (mCCD), followed by characterization as per standard procedures. Ten isolates with Gram negative, catalase positive and oxidase positive characteristics were collected. Antibiotic susceptibility is ascertained through the determination of the inhibited zone and minimum inhibitory concentration (MIC) of five distinct antibiotics against Campylobacter on Muller Hinton agar plates, culminating in a comprehensive assessment after a 24-hour incubation duration. The antibiotic susceptibility results underscore substantial diversity in Campylobacter isolates among meat samples, thereby accentuating discernible distinctions among the various antibiotic products. The research also evaluated the suitability of 5 commercial probiotic products (re-named as A, B, C, D, and E for fair assessment) by examining their impact on the growth of Campylobacter colonies. The antimicrobial effect of probiotics against Campylobacter is assessed using the agar well diffusion assay and co-culture method. We obtained consistent results from two methods, indicating no variation in Campylobacter species among meat samples but significant variations among probiotic products. The outcomes of this research provide valuable insights into the antimicrobial potential of each probiotic and antibiotic on Campylobacter, informing recommendations for food hygiene practices and underscoring the role of both probiotics and antibiotics in combating Campylobacter infections.